Practical Application of the Aqueous ‘Sulfonyl-Azide-Free’ (SAFE) Diazo Transfer Protocol to Less α-C–H Acidic Ketones and Esters - Dar’in, Dmitry; Kantin, Grigory; Krasavin, Mikhail (Synthesis, 2019)
The earlier described ‘sulfonyl-azide-free’ (‘SAFE’) protocol for diazo transfer to CH-acidic 1,3-dicarbonyl compounds (and their similarly activated congeners) has been extended to the less reactive monocarbonyl substrates, which previously required a separate activation step. Formylation in situ, followed by the addition of an optimized amount of the ‘SAFE cocktail’ (obtained by mixing sodium azide, potassium carbonate, and m-carboxybenzenesulfonyl chloride in water) led to the formation of the desired diazo compounds, which were isolated by extraction in moderate to excellent yields, and, in most cases, with no need for additional purification.
Keywords: diazo transfer; water solubility; formylation; deformylation; C–H acidity